IMMUNOREGULATION OF BLOOD SERUM ESTRADIOL AND PROGESTERONE LEVELS IN POSTMENOPAUSAL WOMEN - A. N. Glushkov (SPb RAACI, 2019)
Specific antibodies against estradiol (Es) and progesterone (Pg) are known to modulate blood serum concentrations of these hormones and their biological effects after immunization of animals. It was suggested that specific IgA-Es and IgA-Pg could influence on Es and Pg levels in human blood serum. The purpose of this study was to identify the suggested correlations between serum Es and Pg and specific IgA-Es and IgA-Pg in postmenopausal healthy women (HW) and breast cancer patients (BCP). The serum levels of Es, Pg, IgA-Es and IgA-Pg were studied in 226 HW and 633 BCP by means of solid-phase immunoassay. The following results were obtained. The levels of Es in BCP (0.25 nmol/l) were higher than in HW (0.16; р < 0.0001). The levels of Pg were lower (0.79 vs 0.87; р < 0.0001), and individual Pg/Es ratios were lower (3.19 vs 6.64; р < 0.0001). Individual IgA-Pg/IgA-Es ratios correlated with decrease of Es (rs = -0.15; p = 0.029), with increase in Pg (rs = 0.38; р < 0.0001), and with increased Pg/Es ratio (rs = 0.29; р < 0.0001) in healthy women. Similar correlations were determined in BCP (correspondingly: rs = -0.14, р < 0.001; rs = 0.1, р = 0.009; rs = 0.15, р < 0.0001). The decrease of Es and increase of Pg and Pg/Es in BCP were less significant than in HW: the a quotients in regression у = ах+b (y = hormones levels and x = antibodies levels) in BCP were 3 to 4-fold lower than in HW. These peciliarities of interrelations between hormones and specific antibody levels were revealed only in ER+/PR+ BCP but not in ER+/PR- and ER-/PR- BCP. In conclusion, we have confirmed a suggestion about participation of specific antibodies in regulation of steroids levels in human blood serum. The immune regulation of hormonal status was weakened in BCP.